REKONDISI MESIN TRIMMING - , GEGER SUSILO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A trimming mechine mechine is an oil seal slicer witch is very important in industrial world. A trimming machine is made to improve the quality of the oil seal cut, with trimming machine, producers also can quicken the process of production, a trimming machineâs speed can be very high so that the work can be more efficient and can save the time and the product cost. In the process, the production can be improved to fulfill the market needs, the result of the improvisation on the trimming machine is that it can help the operator in setting the item commutation so that the efficiency of the machine can be improved. A trimmingachine uses electrical and pneumatic power, the electrical and pneumatic power, the electricity is used to activate the spindle engine and the control system which uses PLC, while pneumatic power is used to move the valve and cylinder selenoide air in the trimming process, the selenoide valve is used to control the pneumatic system which is used in the trimming machine.